Soil water regime of grassland communities along subtle topographic gradient in the Flooding Pampa (Argentina) - Carla E. DI BELLA; Gustavo G. STRIKER; Juan LORETI; Diego J. COSENTINO; Agustín A. GRIMOLDI (Soil and Water Research, 2016)
Three plant communities positioned along a subtle topographic gradient, referred to as upland, intermediate, and lowland positions, characterize the landscape of the Flooding Pampa grasslands of Argentina. Although it is believed that the structure and functioning of the plant communities at each position are in close relationship with their hydric regime, this has never been quantified. More than 800 measurements of soil water content during four years, along with soil water retention curves, and physical and chemical parameters of soils were assessed at each position. Results showed that water availability during the year varied among the positions in accordance with differences in hydrological balance and soil water retention capacity of each of them. Water retention increased in relation to clay and organic matter content from the upland to the lowland position. The upland position, with more soil sand content, registered severe drought events during late spring and summer, without flooding periods in any season. The intermediate and lowland positions, with more soil clay content, remained flooded for several weeks during winter and spring, and they manifested less severe summer droughts than the upland position. Moreover, the lowland position was more hydromorphic than the intermediate one. These spatial and temporal variations of water regime and soil parameters characterizing the upland, intermediate, and lowland positions concur with different plant communities associated with each of them.